Perbedaan Kemampuan Belajar Bahasa Arab Antara Mahasiswa Lulusan Pesantren dan Luar Pesantren - Akbar, Faisal; Azizah, Fitri Nur; Febriani, Melisa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out whether there are differences in Arabic language learning abilities between students who graduated from Islamic boarding schools and students who graduated from outside Islamic boarding schools. This research was conducted at the North Sumatra State Islamic University, Arabic Language Education study program and involved 5 students who graduated from Islamic boarding schools and 5 students who graduated from outside Islamic boarding schools. The method used is a quantitative research method with parametric statistical tests of correlated samples. From the research conducted, it was found that there were differences in Arabic language learning abilities between students graduating from Islamic boarding schools and graduates from outside Islamic boarding schools.